Height, body mass index and prostate cancer risk and mortality by way of detection and cancer risk category. Issue 12 (25th June 2020) - Jochems, Sylvia H. J.; Stattin, Pär; Häggström, Christel; Järvholm, Bengt; Orho‐Melander, Marju; Wood, Angela M.; Stocks, Tanja
Abstract: Obesity is a risk factor for advanced, but not localised, prostate cancer (PCa), and for poor prognosis. However, the detection of localised PCa through asymptomatic screening might influence these associations. We investigated height and body mass index (BMI) among 431 902 men in five Swedish cohorts in relation to PCa risk, according to cancer risk category and detection mode, and PCa‐specific mortality using Cox regression. Statistical tests were two‐sided. Height was positively associated with localised intermediate‐risk PCa (HR per 5 cm, 1.03, 95% CI 1.01‐1.05), while overweight and obesity were negatively associated with localised low‐ and intermediate‐risk PCa (HRs per 5 kg/m 2, 0.86, 95% CI 0.81‐0.90, and 0.92, 95% CI 0.88‐0.97). However, these associations were partially driven by PCa's detected by asymptomatic screening and, for height, also by symptoms unrelated to PCa. The HR of localised PCa's, per 5 kg/m 2, was 0.88, 95% CI 0.83 to 0.92 for screen‐detected PCa's and 0.96, 95% CI 0.90 to 1.01 for PCa's detected through lower urinary tract symptoms. BMI was positively associated with PCa‐specific mortality in the full population and in case‐only analysis of each PCa risk category (HRs per 5 kg/m 2, 1.11‐1.22, P for heterogeneity = .14). More active health‐seeking behaviour among tall and normal‐weight men may partially explain their higher risk of localised PCa. The higher PCa‐specific mortality among obese men across all PCa risk categories in our study suggests obesity as a potential target to improve the prognosis of obese PCa patients. Abstract : What's new? While body mass index and height are linked to prostate cancer risk, how these factors are related to specific risk categories, including localized and advanced disease, remains uncertain. In this investigation of body size and prostate cancer risk, height was positively associated with localised, intermediate‐risk prostate cancer, and overweight and obesity were associated with lower risks of localised low‐ and intermediate‐risk prostate cancers. These associations were partially driven by asymptomatic screening, suggesting that increased screening behavior among tall and normal‐weight men contributes to their elevated risk of localised prostate disease. Relatively high prostate cancer‐specific mortality among obese men flags elevated BMI as a key prognostic factor for prostate malignancy.